2018
DOI: 10.1371/journal.pone.0208944
|View full text |Cite
|
Sign up to set email alerts
|

WRF-Chem modeling of particulate matter in the Yangtze River Delta region: Source apportionment and its sensitivity to emission changes

Abstract: China has been troubled by high concentrations of fine particulate matter (PM2.5) for many years. Up to now, the pollutant sources are not yet fully understood and the control approach still remains highly uncertain. In this study, four month-long (January, April, July and October in 2015) WRF-Chem simulations with different sensitivity experiments were conducted in the Yangtze River Delta (YRD) region of eastern China. The simulated results were compared with abundant meteorological and air quality observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The monthly BC patterns were slightly different from those in some previous studies in Shanghai, which showed the lowest monthly BC concentration in September (Feng et al, 2014; Wang, He, et al, 2014). The discrepancy of the patterns among different locations in Shanghai is probably affected by the differences in emission sources and the meteorological conditions in different years (Li et al, 2018; Xu et al, 2015). CO, another air pollutant originating from incomplete combustion, showed similar monthly patterns with BC (Figure S3h).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The monthly BC patterns were slightly different from those in some previous studies in Shanghai, which showed the lowest monthly BC concentration in September (Feng et al, 2014; Wang, He, et al, 2014). The discrepancy of the patterns among different locations in Shanghai is probably affected by the differences in emission sources and the meteorological conditions in different years (Li et al, 2018; Xu et al, 2015). CO, another air pollutant originating from incomplete combustion, showed similar monthly patterns with BC (Figure S3h).…”
Section: Resultsmentioning
confidence: 99%
“…The average BC concentration on the 30 haze days was 4.32 ± 1.37 μg/m 3 (0.25 μg/m 3 ), which was significantly higher than that on nonhaze days (1.99 ± 1.08 μg/m 3 (0.06 μg/m 3 )) (Figure 3). Local anthropogenic emissions and meteorological conditions were the major factors contributing to the formation and evolution of haze events in the YRD area (Li et al, 2018; Xu et al, 2015). The higher BC concentrations on haze days also suggested that BC was coemitted and cotransported with other air pollutants from local and remote sources and accumulated under unfavorable weather conditions (Xu et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…During severe haze events, the observed maximum hourly surface-layer PM 2.5 (fine particulate matter with an aerodynamic diameter of 2.5 µm or less) concentration can exceed 1000 µg m −3 (Z. Sun et al, 2016;, which can significantly influence visibility (Li et al, 2014), the radiation budget (Steiner et al, 2013), atmospheric circulation (Jiang et al, 2017), cloud properties (Unger et al, 2009), and human health (Hu et al, 2014;Guo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, input emission data used in each study may have been the main reason for the differences in the results of each source apportionment simulation. The zero-out method used in this study is a special case of the brute-force method which has been widely used to estimate the contributions of local and non-local emission sources or sectoral emission sources to the concentration of air pollutants at specific locations [32,[58][59][60]. The BFM quantifies the contribution of one or more emission sources to the concentration of air pollutants at specific locations through a series of simulations including a base case simulation where no changes to emission sources are made and other simulations with modified emissions.…”
Section: Contributions Of Different Emission Sectors Inside Hanoi To ...mentioning
confidence: 99%